Knowledge and Perspective regarding Adolescent Sexual and Reproductive Health Among Adolescents in Selected Schools of Birendranagar Mucinipality of Surkhet, Karnali Province - Sapkota, Shakuntla; Chaudhari, Aitawari; Rawal, Prabha; Paudel, Khechar Nath; Giri, Pratima (NPRC Journal of Multidisciplinary Research, 2024)
Introduction: Adolescence is the period of transition and opportunity in which physical, psychological, and social changes occur. Adolescents have various sexual and reproductive health problems like teenage pregnancy, abortions, sexually transmitted infections, etc. This study was designed to investigate the adolescence’s knowledge and perspective towards sexual and reproductive health in Birendranagar Municipality of Surkhet, Nepal. Methods: A descriptive cross-sectional study was designed to investigate the adolescence’s knowledge and perspective towards sexual and reproductive health in Birendranagar Municipality of Surkhet, Nepal. Structured questionnaires were developed in close-ended form and administered to a selected sample population. The questionnaire contained questions in five domains: social-demographic data, knowledge regarding adolescents’ sexual life, knowledge on reproductive health and safe sexual behavior, practices of sexual behaviors, and other contextual factors. In this study, a total of 328 respondent’s questionnaires were issued, and 312 were valid. The response rate was 95%. Results: There were a total of 312 participants, 174 boys, 137 girls, and 1 third gender involved in the study. Around 80% of adolescents were from secondary level education, and only 20% were from basic level education. Nearly half of the adolescents had inadequate knowledge of adolescents’s sexual and reproductive health. Sexual abuse, unwanted pregnancy, early marriage, and STIs were the common reproductive health problems faced by adolescents. Conclusion: So, based on the above findings, government of Nepal should make different plans and policies to solve the adolescent’s sexual and reproductive health problems.